Use of Green Supply Chain Management Principles in Household level in Nepal - Pandey, Krishna Prasad; Jirojkul, Sudjai; Techato, Kuaanan; Karki, Tej Bahadur; Ojha, Bhoj Raj; Bharati, Cheta Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: Environmental sustainability has emerged as a major global issue, triggered by industrialization and environmental pollution. Green Supply Chain Management (GSCM), which combines environmentally responsible practices in supply chain operations, has been identified as an important approach to counter environmental issues. Although GSCM has been widely researched in industrial settings, the use of GSCM principles in household settings has not been adequately investigated, especially in developing nations such as Nepal, where conventional energy sources and transportation practices create major environmental and health issues. Objectives: The objectives of this research were to examine the use of GSCM principles in household settings in Nepal, specifically in terms of energy usage for cooking and lighting, as well as transportation trends. Methods: The research design used in the study was quantitative, relying on secondary data analysis. Time series data ranging from 2012/13 to 2022/23 were sourced from various public sources in Nepal, including the National Population and Housing Census (2021), the Economic Survey, and Nepal Oil Corporation publications. The study aimed to analyze trends in household energy consumption (firewood, LPG, electricity, etc.), lighting types, vehicle registration, petroleum products, etc. Findings: The results show a substantial dependence on conventional biomass fuels, with 51% of households and 75% in the rural areas using firewood for cooking. Although access to electricity for lighting is high (92.2%), there are regional inequalities. The transportation sector indicates a sharp rise in the number of vehicles, especially motorcycles, although there is a positive development in the use of electric vehicles such as e-rickshaws and safa tempos. The use of petroleum products, particularly petrol and diesel, has increased substantially, leading to air pollution. The use of cleaner fuels such as LPG and electricity for cooking has had limited success in the rural areas. Conclusion: The research reveals an existing gap in the practical application of GSCM strategies, such as the use of cleaner inputs, energy efficiency, and minimizing waste and emissions, at the household level in Nepal. The ongoing dependence on polluting energy sources, coupled with an increasing trend of conventional vehicles, reveals an alarming situation of environmental and health hazards. Nevertheless, the increasing use of renewable energy sources for lighting and electric vehicles offers an opportunity for sustainable development. Novelty: This research is novel in its approach as it attempts to break away from the conventional GSCM discourse, which is mainly centered around industries and businesses. This research offers a comprehensive analysis of household energy and transportation trends in Nepal, covering a decade, from a GSCM perspective.